Pengaruh Manajemen Laba Terhadap Kinerja Keuangan Pada Perusahaan Yang Telah Menggunaan Sak Konvergensi Ifrs Mandatory (Studi Empiris Pada Perusahaan Manufakur Yang Terdaftar Di Bei Tahun 2013-2017) - Ana Marfungatun; Eliya Isfaatun (Jurnal Solusi, 2019)
This study aims to obtain empirical evidence about the effect of earnings management on financial performance. Earnings management is the act which is conducted by manager to maximize, minimize, or do income smoothing of company’s profit. Managers can affect their company’s market value by do earnings management, such as make their profit always increase every year to show their good job financial performance. Independent variable if this study is earnings management that measured by discretionary accruals and dependent variable is financial performance that measure by return on assets. This population of the study was all of the manufacturing companies on the Indonesia Stock Exchange for five years from 2013 to 2017, while the sample of the research was determined by purposive sampling method to obtain 51 sample companies. The study analyzed one independent variables using secondary data in the form of panel data with a cross-section in 51 companies and a time series of five years. The analysis was regression with a random effect specification. The analysis was regression with a random effect specification the results this study showed that earnings management affect return on assets significantlye.